Structural and dynamic insights into supra-physiological activation and allosteric modulation of a muscarinic acetylcholine receptor - Xu, Jun; Wang, Qinggong; Hübner, Harald; Hu, Yunfei; Niu, Xiaogang; Wang, Haoqing; Maeda, Shoji; Inoue, Asuka; Tao, Yuyong; Gmeiner, Peter; Du, Yang; Jin, Changwen; et al. (Nature Communications, 2023)
The M2 muscarinic receptor (M2R) is a prototypical G-protein-coupled receptor (GPCR) that serves as a model system for understanding GPCR regulation by both orthosteric and allosteric ligands. Here, we investigate the mechanisms governing M2R signaling versatility using cryo-electron microscopy (cryo-EM) and NMR spectroscopy, focusing on the physiological agonist acetylcholine and a supra-physiological agonist iperoxo, as well as a positive allosteric modulator LY2119620. These studies reveal that acetylcholine stabilizes a more heterogeneous M2R-G-protein complex than iperoxo, where two conformers with distinctive G-protein orientations were determined. We find that LY2119620 increases the affinity for both agonists, but differentially modulates agonists efficacy in G-protein and β-arrestin pathways. Structural and spectroscopic analysis suggest that LY211620 stabilizes distinct intracellular conformational ensembles from agonist-bound M2R, which may enhance β-arrestin recruitment while impairing G-protein activation. These results highlight the role of conformational dynamics in the complex signaling behavior of GPCRs, and could facilitate design of better drugs.
CRIS-Team Scopus Importer:2023-02-03
Keywords: Cryoelectron microscopy; G protein-coupled receptors; Solution-state NMR